2019
DOI: 10.2147/rru.s204507
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of tumor cytoreduction in metastatic prostate cancer</p>

Abstract: Objective: To assess the impact of tumor cytoreduction on cancer outcomes and patient survival in metastatic prostate cancer. Patients and methods: It is a prospective study spanning a two-year period between October 1st 2015 and March 31st 2017. We enrolled 102 cases of metastatic hormone-sensitive prostate cancer. Fifty-seven (57) patients had exclusively androgen deprivation therapy (ADT) (group 1) and 45 had, in addition, an open prostatectomy or Transurethral resection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 17 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…In patients with advanced and metastatic prostate cancer, surgical and medical androgen deprivations were the commonest modalities offered [8–10, 1215, 19, 21–23]. Yeboah et al [21] clearly emphasized the use of neoadjuvant hormonotherapy, androgen deprivation therapy, external beam radiation, brachytherapy, channeling TURP, and transurethral incision of the prostate as modalities in the management of patients reported for advanced and metastatic prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In patients with advanced and metastatic prostate cancer, surgical and medical androgen deprivations were the commonest modalities offered [8–10, 1215, 19, 21–23]. Yeboah et al [21] clearly emphasized the use of neoadjuvant hormonotherapy, androgen deprivation therapy, external beam radiation, brachytherapy, channeling TURP, and transurethral incision of the prostate as modalities in the management of patients reported for advanced and metastatic prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Androgen deprivation can be achieved using LHRH analogues, bilateral orchidectomy, or LHRH analogues + first-generation antiandrogen [2]. However, the STAMPEDE and CHAARTED trials have shown an overall survival benefit in high volume (mCNPC) receiving continuous androgen-ablation therapy and docetaxel (chemo-hormonotherapy) [23, 29, 31, 32]. Results from the STAMPEDE and LATITUDE studies also projected a greater median overall survival with abiraterone and prednisone in addition to androgen deprivation therapy for locally advanced and metastatic prostate cancer as compared to ADT alone [33, 34].…”
Section: Discussion Of the Standard Guidelines For Advanced/metastmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence level was relatively low, and our research found a clue that TURP could play an important role in metastatic PCa. [ 9 , 16 ]…”
Section: Discussionmentioning
confidence: 99%